Right-wing Extremist Group Survival in Finland – a Qualitative Case Analysis of Soldiers of Odin and the Nordic Resistance Movement - Kotonen, Tommi (Perspectives on terrorism, 2023)
The survival of right-wing extremist (RWE) groups is a relatively understudied topic despite its relevance to such matters as the prevention and countering of violent extremism. In this article we investigate why some RWE groups are able to survive for a protracted period of time. Updating previous knowledge on group survival, our study analyses the life trajectories of two Finnish RWE organisations, Soldiers of Odin (SOO) and the Nordic Resistance Movement (NRM), as examples of how and why groups survive. SOO is a vigilante street patrol organisation with a network-like structure and no clear commitment to any particular RWE ideology, while the NRM, by contrast, is a more hierarchical national socialist group. The lifespan of both groups far exceeds the average duration of Finnish extremist organisations, rendering them suitable objects of research for a study on group survival. The topic is explored through empirical observation of the two groups and combined with insights from previous studies and theories. The main body of data consists of material on SOO and the NRM that the authors have gathered during the past seven years. The study is carried out as a contextualised and thematic qualitative analysis based on a framework of external and internal factors on group survival that previous research has formulated. Our study partly supports and partly challenges previous findings on the factors deemed as crucial to group survival while also demonstrating that individual factors may influence the fate of RWE groups in more than just one way.